Detection of heavy metals concentration in vegetables and analyze the health risks - Gurmu, Solomon Legesse; Mengistu, Fekede Weldekidan; Beyene, Atsedu Yeshwalul; Ketema, Bizunesh; Tadesse, Birhanu Million (Intelektual Pustaka Media Utama, 2025)
Heavy metals are elements found in Earth’s crust but introduced into soil and water bodies by human activities. They are not biodegradable, so they persist for a long time in the environment. Heavy metals are incorporated into to human body through the food chain, resulting in various health problems. Akaki Rivers, which are major water sources in Addis Ababa, are contaminated with various wastes, including heavy metals. This research aimed to detect heavy metal concentration in cabbage, potato, tomato, and beetroot irrigated with the Akaki Rivers and evaluate associated health risks. Following the vegetable sample collection, a laboratory-based study was used in sample processing, digestion, and heavy metal detection. Mean concentration (mg/kg dry weight) of Cd (26.11-26.34), Pb (17-33.84) in all samples, and Hg (0.124) in beetroot exceeded the permissible limits set by WHO/FAO. The HRI of Cd (28.3-140.96), Pd (10.9-27.35), both in adults and children, and Hg (1.727 for children) exceeded the safe limit (<1). The health of adults and children is at risk due to Cd, Pb, and Hg, with children facing approximately 2.5 times higher. Minimization of the release of wastewater into the Akaki Rivers, and dietary diversification should be encouraged, and the health of permanent consumers should be checked.